2021
DOI: 10.3390/cryst11080951
|View full text |Cite
|
Sign up to set email alerts
|

Paraffin Wax [As a Phase Changing Material (PCM)] Based Composites Containing Multi-Walled Carbon Nanotubes for Thermal Energy Storage (TES) Development

Abstract: Thermal energy storage (TES) technologies are considered as enabling and supporting technologies for more sustainable and reliable energy generation methods such as solar thermal and concentrated solar power. A thorough investigation of the TES system using paraffin wax (PW) as a phase changing material (PCM) should be considered. One of the possible approaches for improving the overall performance of the TES system is to enhance the thermal properties of the energy storage materials of PW. The current study i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…The peak seen at 3000 cm-1 corresponds to CNT and this is due to stretching of the C=C bonds. The bonds resulting from C-C stretching of the CNT structure are seen at 1000 cm-1 (Almousa et al, 2021). No new bond was formed with the addition of CNT to the PE-wax/waste LDPE mixture, which clarified that there was no interaction between them other than physical interaction while forming the composite.…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The peak seen at 3000 cm-1 corresponds to CNT and this is due to stretching of the C=C bonds. The bonds resulting from C-C stretching of the CNT structure are seen at 1000 cm-1 (Almousa et al, 2021). No new bond was formed with the addition of CNT to the PE-wax/waste LDPE mixture, which clarified that there was no interaction between them other than physical interaction while forming the composite.…”
Section: Resultsmentioning
confidence: 89%
“…Waste materials such as industrial by-products, agricultural residues, and municipal solid waste can be used as fillers in C-PCM, providing an environmentally friendly solution for waste management. Several studies have investigated the use of waste materials in C-PCM and have shown that these materials can improve the thermal properties and performance of the TES system while also reducing costs and environmental impacts (Almousa et al, 2021;Ghani et al, 2021;Harmen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The understanding of beeswax’s thermal behavior is critical in identifying the thermal degradation (or stability) of the substance, the conversion of the substance, and the product formation. The beeswax samples were placed in alumina crucibles under a 100 mL/min flow rate of nitrogen and a 10 °C/min heating rate, using a thermo-balance Discovery SDT 650 (TA Instruments, New Castle, DE, USA) [ 21 ].…”
Section: Methodsmentioning
confidence: 99%
“…Air-10 The analysis showed the presence of paraffin oil that could be related to the use of paraffin wax as a protective layer of the anode material or separator [25]. The paraffin oil was released during the increase in cell temperature: at about 55 • C, the wax melted and subsequently (>240 • C), it started to decompose [26]. In addition to paraffin oil, the main peaks due to polyethylene oxide (PEO) were identified [27].…”
Section: Identificationmentioning
confidence: 99%